2011
DOI: 10.1007/s11240-011-9957-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of the cyclin gene family in Populus trichocarpa

Abstract: The cell cycle is controlled by the interplay of many different molecules. Foremost in this process are the cyclin family of proteins that serve to regulate the cell cycle by interacting with cyclin-dependent kinases (CDKs). To date, the cell cycle and functions of the cyclin gene family have been extensively analyzed in Arabidopsis, rice, and humans. However, the cyclin gene family in poplar has rarely been researched. In the present study, cyclin genes were predicted in the poplar draft genome sequence by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…D-, CycJ18-, T-, SDS-, and U-type cyclins are not specific to Arabidopsis but are also present in other plants [ 15 ]. For conserved domains, our study indicated that most of the A-, B-, and D-types contained both cyclin_N and cyclin_C domains; however, each of the U- and T-types in all putative cyclins had only cyclin_N without cyclin_C domains, as also reported in Arabidopsis , maize, rice and poplar [ 15 , 18 , 19 , 20 ]. Additionally, together with the structures and motifs of these cyclins, the same types of cyclins in Arabidopsis and legume plants were located in the same clades and shared high sequence similarity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…D-, CycJ18-, T-, SDS-, and U-type cyclins are not specific to Arabidopsis but are also present in other plants [ 15 ]. For conserved domains, our study indicated that most of the A-, B-, and D-types contained both cyclin_N and cyclin_C domains; however, each of the U- and T-types in all putative cyclins had only cyclin_N without cyclin_C domains, as also reported in Arabidopsis , maize, rice and poplar [ 15 , 18 , 19 , 20 ]. Additionally, together with the structures and motifs of these cyclins, the same types of cyclins in Arabidopsis and legume plants were located in the same clades and shared high sequence similarity.…”
Section: Discussionsupporting
confidence: 79%
“…Phylogenetic analysis indicated that all putative legume cyclins were classified into ten types (A-, B-,C-, D-, H-, L-, T-, U-, SDS-, and J18-types), sharing the same types with Arabidopsis , whereas the D-type was the largest clade in the legume species, and the CycB-like types, including CycBL;1-8, were specific to Medicago, lacking any clear homologues in Arabidopsis , common bean and soybean. Likewise, F-type cyclins, lacking clear homologues in Arabidopsis , were unique to rice, and Q- and Z-types were defined as new putative types of poplar cyclin genes [ 19 , 20 ]. D-, CycJ18-, T-, SDS-, and U-type cyclins are not specific to Arabidopsis but are also present in other plants [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 1 g sample was placed into a 50 ml steel jar together with a steel bead and frozen by liquid nitrogen for more than 10 min firstly, and then the jar was set in a high throughput ball mill (DHS, Beijing, China) for powdering the samples for 2 min. Total RNA was isolated by the improved cetyl trimethylammonium bromide (CTAB) method (Dong et al 2011). A 2 μg of total RNA was reverse transcribed by means of the PrimeScript RT reagent Kit (TaKaRa, Dalian, China) to generate cDNA.…”
Section: Abbreviations Materials and Methodsmentioning
confidence: 99%
“…& A. Gray ex Hook., hereafter called poplar; Dong et al, ), but the evidence presented was not strong enough because an extensive phylogenetic analysis was lacking. In addition, because representatives of non‐seed plants have not been included, it remains unclear how plant cyclins have evolved and whether the previously defined groups and subgroups are reasonable.…”
mentioning
confidence: 99%